Manufacturing and Applications of Ceramic Matrix Composites in the Automotive Industry: Advancements in Ceramic Matrix Composites for Enhanced Automotive Performance (Journal of Advances and Scholarly Researches in Allied Education, 2020)
A reduction in exhaust emissions, fuel consumption, and vehicle weight is necessary for theadvancement of the modern automobile industry at the same time as an increase in safety and vehicleperformance. The introduction of new modern materials with increased qualities in place of traditionalmaterials can fulfill these difficult and mutually contradictory conditions. This is a trend that has beengoing on for a long time and is expected to continue into the next decade. For automobile parts requiringgreat mechanical endurance and strong resistance to extreme temperatures with a decreased bulk,ceramic-based composite materials (CMCs) are becoming increasingly popular. Many different forms ofceramic base composites are routinely utilized as matrices, including oxide, silicon carbide (SiC),carbon, and others. CMCs are now employed in the production of individual vehicle engine components,valves, turbine parts, exhaust and intake systems, brake disks, and other brake system components,amongst other things.